Development of STATCOM to Improve Voltage Sag Due to Starting of 5 kilowatt Induction Motor - Huweg, Abdurrahman Feturi S. (2005)
Voltage sags are the most frequent power quality problems for many industrial processes. Due to the wide usage of sensitive electronic equipment in many fields as, electronic controller, communication and computers, even voltage sags which last for only few tenths of a second may cause production stops with considerable associated costs; these costs include production losses, equipment restarting, damaged or lower-quality product and reduced customer satisfaction.